Assessment of knowledge, attitude, and practice regarding veterinary antibiotic use among animal farmers in Barangay Parada, Santa Maria, Bulacan - Acosta, Jayson M.; Mallari, Jonash N.; Silva, Kristel Abby G. (2017)
The irrational use of antimicrobials in the veterinary sector greatly contributes to the emergence of antimicrobial resistance (AMR) in humans. However, there is a paucity of information on the use of such drugs among animal farmers, especially in developing countries like the Philippines. This pilot study aims to assess the knowledge, attitude, and practice (KAP) among animal farmers regarding veterinary antibiotic use. A descriptive, cross sectional study was employed among the farmers of Barangay Parada, Santa Maria, Bulacan. Using total enumeration, data from 144 farmers were collected using a validated and pretested structured questionnaire. Analysis was done using Microsoft Excel® 2016 and Stata® MP 64 version 13. Results showed that most farmers had low level of knowledge on antibiotic resistance and use. However, they were found to have a positive attitude in using antibiotics. Moreover, most farmers exhibited poor practice regarding antibiotic use. Statistical analysis of the data using either Chi square or Fisher?s exact test showed that educational attainment, position in farm, role in antibiotics, and years of experience had a signification association (p<0.05) to knowledge. It is hoped that this study will provide baseline information for future studies on the contribution of the animal industry to AMR as well as key strategies for interventions in its prevention and control.